1998
DOI: 10.1021/jp9822283
|View full text |Cite
|
Sign up to set email alerts
|

Anhydride Ring Chemistry at a Metal Surface

Abstract: The adsorption of phthalic anhydride on clean and oxygen predosed Cu{110} surfaces has been studied by Fourier transform infrared spectroscopy in the temperature range 95−300 K. Further characterization of the adsorbed species and its thermal stability on these surfaces has been obtained from thermal desorption measurements. A variety of species are produced on the clean surface including the parent molecule, one in which the anhydride ring has been cleaved and one following the loss of a CO unit which is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
3
17
1
1
Order By: Relevance
“…However, there are three additional peaks centered at 1775, 1790, and 1853 cm −1 that cannot be attributed to any vibrational modes of PA. In fact, they correspond very well to those of phthalic acid anhydride (PAA) . In our previous work on PA on MgO(100)/Ag(100), we observed that a small fraction of PAA was formed upon PVD of PA and is co‐adsorbed onto the surface at low temperature …”
Section: Resultssupporting
confidence: 58%
“…However, there are three additional peaks centered at 1775, 1790, and 1853 cm −1 that cannot be attributed to any vibrational modes of PA. In fact, they correspond very well to those of phthalic acid anhydride (PAA) . In our previous work on PA on MgO(100)/Ag(100), we observed that a small fraction of PAA was formed upon PVD of PA and is co‐adsorbed onto the surface at low temperature …”
Section: Resultssupporting
confidence: 58%
“…Thirdly, the orientation of the plane of the carboxylate units nearly parallel to the surface is proposed in our model, which is in accordance with other structural models [13] and the fact that carboxylic acids bind to copper in a bidentate fashion. [28,31] However, in contrast to Cu(100) where two mixed adsorption geometries involving one and two carboxyl groups of TMA were suggested to explain striped features, [13] the present structure is based on one adsorption geometry. The monopodal adsorption geometry reported for trimellitic acid on Cu(100) also differs from the present structure although it has the same structural motiv as IPA.…”
Section: Angewandte Chemiecontrasting
confidence: 55%
“…The nature of the vibrational bands was carefully analyzed using the visualization tool QVibePlot (see ref ). The bands were assigned on the basis of the calculated spectra and previous literature, ,,,, and the most prominent features and assignments are listed in Table . Briefly, the following spectral regions are of relevance for the discussion below.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial phase of BA deposition (Figure a,b) a prominent peak is observed at around 1412 cm –1 shifting to 1423 cm –1 with increasing coverage. Based on previous work, , the band is assigned to the OCO symmetric stretching mode of the surface anchored carboxylate, ν s (OCO). This observation indicates deprotonation and the formation of benzoate species even at 130 K. The corresponding asymmetric OCO stretching mode, ν as (OCO), which we would expected to appear 1550 cm –1 (see refs , , and ) is not observed, indicating the formation of a symmetric carboxylate.…”
Section: Resultsmentioning
confidence: 99%